The role of the supreme courts: in the search of the balance between private and public interests in civil procedure - Цувіна, Тетяна Андріївна (Problems of legality, 2020)
The article is devoted to the analysis of the problem issues of the role of the supreme courts in common law and civil law legal traditions through the prism of models of proceedings in such courts in order to determine the general trends in this field. The author analyzes three main models of the proceedings in courts of the highest instance: a second appeal, a cassation and a revision. A second appeal model refers to the common law countries, and cassation and revision models refer to civil law countries. Analysis of the civil procedural legislation and resent reforms of civil procedure in European countries give grounds to conclude that there is a strong tendency to convergence between cassation and revision models nowadays. The author analyzes two main approaches to the identification of the role of supreme courts in modern societies: conception of private interests and conception of public interests. The cassation model of appeal reflects the priority of the private legal interests in the activity of the supreme courts, instead the second appeal model is the predominance of the public legal foundations. More promising direction from the point of view of achieving the tasks of civil justice is the election at the national level of a model in which preference is given to public-law interest during proceedings in the highest court which is reflected in revision model. The recent proposed changes to the civil procedural legislation of Ukraine testifies to the strong tendency of approximation of the national cassation proceedings model to the revision model. Such situation is justified and reflects the current trends in the development of civil procedural legislation in European countries.